Credit conditions indices: Controlling for regime shifts in the Norwegian credit market - Eilev S. Jansen; Tord S. H. Krogh (Statistics Norway, Research Department, 2011)
The interaction between financial markets and the macroeconomy can be strongly affected by changes in credit market regulations. In order to take account of these effects we control explicitly for regime shifts in a system of debt equations for Norway using a common, flexible trend. The estimated shape of the trend matches the qualitative development in the regulations, and we argue that it can be viewed as a measure of relative credit availability, or credit conditions, for the period 1975-2008 – a credit conditions index (CCI). This entails years of strict credit market regulations in the 1970s, its gradual deregulation in the 1980s, followed by a full-blown banking crisis in the years around 1990 and the development thereafter up to the advent of the current financial crisis. Our study is inspired by Fernandez-Corugedo and Muellbauer (2006), which introduced the methodology and provided estimates of a CCI for the UK. The trend conditions on a priori knowledge about changes in the Norwegian regulatory system, as documented in Krogh (2010b), and it shows robustness when estimated recursively.
Keywords: E44; G21; G28; 330; financial credit conditions; flexible trend; financial deregulation; household loan.